An evolution of pontoon traps for cod fishing (Gadus morhua) in the southern Baltic Sea - Ljungberg, Peter; Königson, Sara; Lunneryd, Sven-Gunnar (Frontiers in Marine Science, 2022)
With increasing seal populations in the Baltic Sea comes growing interaction between seals and coastal fisheries. The impact of seals, mainly grey seal (Halichoerus grypus), on fisheries can be reduced by implementing of seal-safe fishing gear, which hinders seal access to catches. One successful solution is the introduction of a modified seal-safe trap net, the pontoon trap. In this study, pontoon traps were modified for use in cod (Gadus morhua) fisheries in the southern Baltic Sea. Three aspects of the pontoon trap design were tested for their effects on catch rates: (1) leader net mesh size; (2) leader net length; and (3) fish chamber position. The greatest catch rates were obtained using a leader net with a 100 mm center-knot to center-knot mesh-size on a bottom-set fish chamber while there was no difference in cod catch rates in relation to leader net length. There was no seal-induced damaged cod in the pontoon traps during any of the trials. Cod catch rates using the pontoon trap were also compared to those of the cod gillnet fishery in the same area. The comparison showed that during specific fishing occasions, multiple pontoon traps may have similar catch rates to gillnets.